Microsoft SharePoint 2003 unleashed - Spence, Colin (Sams, 2005)
As businesses attempt to maximize every employee hour, knowledge management and collaboration tools like SharePoint 2003 have become more popular. Now businesses turn their attention to maximize this tool. Microsoft SharePoint 2003 Unleashed, Second Edition can show you how to do this. Revised based on reader feedback, this new edition delves into the power of SharePoint 2003 by going deep inside topics that include: Migrating to SharePoint 2003 Planning and Implementing a SharePoint 2003 Environment Managing a SharePoint 2003 Environment Extending the SharePoint 2003 Environment SharePoint 2003 technologies are designed to make it easier for everyone on a network to find and manage information. Microsoft SharePoint 2003 Unleashed, Second Edition makes it easier to get there.